The study of lower limb EMG signals between male and female Muslim during pertaining to sujud postures in solat / H. Harun, N.F. Mohd Nasir and A.F. Salleh - Harun, H.; Mohd Nasir, N. F.; Salleh, A. F. (UiTM Press, 2016)
Electromyography signal level in term of %MVC at lower limb muscles on static posture of feet during sujud (prostration) in solat had been studied based on the sayings of Prophet Muhammad (hadiths). Gastrocnemius and Tibialis Anterior were the chosen muscles as both are the major lower leg muscles on the lower limb part. A total of 10 male and 10 female subjects had participated in this study. The EMG data signal results were analyzed statistically using the PairedSamples T Test as all the data are normally distributed. The statistical result showed that there is no significant difference of the muscles' signal on the respective posture between male and female. The result of EMG level in term of %MVC between male and female showed that during pertaining to sujud posture, Gastrocnemius muscles are more active in male while Tibialis Anterior muscles are more active in female.